Controllability of psi-Hilfer fractional differential equations with infinite delay via measure of noncompactness - Haque, Inzamamul; Ali, Javid; Nieto, Juan J. (Nonlinear Analysis: Modelling and Control, 2024)
In this article, we study the controllability of ψ-Hilfer fractional differential equations with infinite delay. Sufficient conditions for controllability results are obtained by using the notion of the measure of noncompactness and the Mönch fixed point theorem. The novel feature of this study is to inquire into the controllability notion by using ψ-Hilfer fractional derivative, the generalized variant of the Hilfer derivative. Finally, we provide a numerical example to illustrate our main result.